2019
DOI: 10.1007/s40262-018-00732-2
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Tuberculosis Treatment Through Model-Informed Dosing of Rifampicin

Abstract: Background and objective This study proposes a model-informed approach for therapeutic drug monitoring (TDM) of rifampicin to improve tuberculosis (TB) treatment. Methods Two datasets from pulmonary TB patients were used: a pharmacokinetic study (34 patients, 373 samples), and TDM data (96 patients, 391 samples) collected at Radboud University Medical Center, The Netherlands. Nine suitable population pharmacokinetic models of rifampicin were identified in the literature and evaluated on the datasets. A model d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…As EBEs and shrinkage are dependent on the sampling design, different EBEs for each individual would have been achieved with a different sampling design. However, the sampling PK design used in this work is supported by the work by van Beek et al (2019) who identified this sampling design as most informative for deriving EBEs of rifampicin among those evaluated. If a different design for any reason would be applied, the absolute dose prediction error would most likely be higher.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…As EBEs and shrinkage are dependent on the sampling design, different EBEs for each individual would have been achieved with a different sampling design. However, the sampling PK design used in this work is supported by the work by van Beek et al (2019) who identified this sampling design as most informative for deriving EBEs of rifampicin among those evaluated. If a different design for any reason would be applied, the absolute dose prediction error would most likely be higher.…”
Section: Discussionmentioning
confidence: 96%
“…Besides high accuracy in dose predictions, another advantage of a MIPD approach is the limited amount of samples and sampling occasions needed to forecast the next dose. It has previously been shown, that taking merely two blood samples (2 and 4 h post-dose) is sufficient to characterize individual PK parameters (van Beek et al, 2019) when using a model-based approach. In addition, the results of this simulation study demonstrate that two sampling occasions are sufficient to capture the IOV and individual exposure, since the decrease in imprecision and bias in dose predictions was statistically significant when information from two occasions were used to estimate EBEs, compared to only using information from a single occasion (Tables 5 and 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limitations related to the use of model-based dose individualization for TKIs mainly involve the complexity and computational power related to the model building process, and consequently the availability of such models and software to have a direct implementation at the point of care (van Beek et al, 2019). In addition, since the current models are based upon rich, but often more selected, datasets derived from clinical trials they might require further adjustments to represent the parameter distributions of the entire patient population (Keizer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%